PEER REVIEW UNTUK PENGAJARAN KETRAMPILAN MENULIS KALIMAT BAHASA INGGRIS - Listiani Listiani (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2016)
This research aimed to know the effectiveness of peer review for teaching English sentence writing skill to university students in Central Java, Indonesia. An experimental group was treated by implementing peer review, but a control group was not treated. For collecting the data, both groups were given test: pre test and post test. After analyzing using t-test formula, the result showed that t-value (2,890) was higher than t-table (2,048). Therefore, peer review was effective for teaching English sentence writing skill. Key words: peer review, sentence writing skill, teaching English sentence writing skill